Multimodal Patient Blood Management Program Based on a Three-pillar Strategy: A Systematic Review and Meta-analysis. Issue 5 (May 2019) - Althoff, Friederike C.; Neb, Holger; Herrmann, Eva; Trentino, Kevin M.; Vernich, Lee; Füllenbach, Christoph; Freedman, John; Waters, Jonathan H.; Farmer, Shannon; Leahy, Michael F.; Zacharowski, Kai; Meybohm, Patrick; et al.
Abstract : Objectives: To determine whether a multidisciplinary, multimodal Patient Blood Management (PBM) program for patients undergoing surgery is effective in reducing perioperative complication rate, and thereby is effective in improving clinical outcome. Background: PBM is a medical concept with the focus on a comprehensive anemia management, to minimize iatrogenic (unnecessary) blood loss, and to harness and optimize patient-specific physiological tolerance of anemia. Methods: A systematic review and meta-analysis was performed. Eligible studies had to address each of the 3 PBM pillars with at least 1 measure per pillar, for example, preoperative anemia management plus cell salvage plus rational transfusion strategy. The study protocol has been registered with PROSPERO (CRD42017079217). Results: Seventeen studies comprising 235, 779 surgical patients were included in this meta-analysis (100, 886 pre-PBM group and 134, 893 PBM group). Implementation of PBM significantly reduced transfusion rates by 39% [risk ratio (RR) 0.61, 95% confidence interval (CI) 0.55–0.68, P < 0.00001], 0.43 red blood cell units per patient (mean difference −0.43, 95% CI −0.54 to −0.31, P < 0.00001), hospital length of stay (mean difference −0.45, 95% CI −0.65 to −0.25, P < 0, 00001), total number of complications (RR 0.80, 95% CI 0.74–0.88, P <0.00001), and mortality rate (RR 0.89, 95% CI 0.80–0.98, P = 0.02). Conclusions: Overall, a comprehensive PBM program addressing all 3 PBM pillars is associated with reduced transfusion need of red blood cell units, lower complication and mortality rate, and thereby improving clinical outcome. Thus, this first meta-analysis investigating a multimodal approach should motivate all executives and health care providers to support further PBM activities. Abstract : Supplemental Digital Content is available in the text